“There was a virgin forest here; it was all woods”: local perceptions of landscape changes in Northeastern Brazil - Gonçalves, Paulo Henrique; Rego, Antônia Edna Magalhães; Medeiros, Patrícia Muniz de (Ethnobiology and Conservation, 2018)
This paper presents a case study to understand how people from a rural population that has been undergoing intense anthropogenic transformations in recent decades perceive these local landscape changes. We conducted a participatory workshop, during which we used the scoring exercise method to stimulate the participants to rank the plant species that they consider most important for utilitarian and commercial purposes, and we employed the historical chart method to they represent the perceived changes in the availability of agricultural, wood, and medicinal plant resources over the last five decades. In order to further explore the historical chart results, we employed the thematic oral history method with those residents considered by the local people as having a high degree of knowledge about the local forest. Our findings show that people attribute great importance to the species of edible plants in the region, although they perceive them as having a low commercial potential. Regarding the perceived changes in the landscape, people indicated that there were declining areas of forest in the region, and that in the past, agriculture was practiced more intensely. Additionally, people perceive a decline in the availability of plants for wood purposes, and an increase in the availability of plants for medicinal purposes. These results indicate that even small rural populations can undertake significant changes in their surrounding ecosystems over time.